To understand the process, work backwards...
(a+5b)^2 = (a+5b)(a+5b)
= a^2 + 5ab + 5ab + 25b^2
= a^2 + 10ab + 25b^2
2006-12-17 13:55:19
·
answer #1
·
answered by TKD Girl 2
·
0⤊
0⤋
We know (A + B)^2 = A^2 +2.A.B + B^2
Given: a^2 + 10ab + 25b^2 = a^2 + 2.a.5b + (5b)^2
Here, A = a, B = 5b
So a^2 + 10ab + 25b^2 = (a + 5b)^2
Another method:
a^2 + 10ab + 25b^2
= a^2 + 5ab + 5ab + 25b^2 (break the middle term such that 5+5 = 10 = middle term and 5x5 = 25 = last term x first term = 25x1)
= a(a + 5b) + 5b(a + 5b)
= (a + 5b)(a + 5b)
= (a + 5b)^2
Note: If a binomial function is squared, 4 terms are produced, of which two terms are algebraically additive which gives us a TRINOMIAL.
When we factorize a TRINOMIAL, the middle term is broken into two terms appropriately and then factorize.
2006-12-17 14:15:19
·
answer #2
·
answered by Sheen 4
·
0⤊
0⤋
You have expressed the middle term as a sum of two other terms, which enabled you to pair them, and factor to the final result.
Check it here:
a^2+10ab+25b^2 = (to factor this out, we will have to have something that will enable us to extract 5b from 25b^2, and a from a^2; "it" has to form a sum equal to 10ab: we need 10ab = something*ab + somethingelse*ab; other times it might not be expressed as two identical terms)
= a^2 + 5ab + 5ab + 25b^2 (this time, 5ab + 5ab might match our needs; if the middle term was negative, you would need a difference, e.g. -5ab-5ab)
= a(a+5b) + 5b(a+5b)
= (a+5b)(a+5b)
= (a+5b)^2
2006-12-17 14:13:23
·
answer #3
·
answered by Mirta G 2
·
0⤊
0⤋
10ab is used to check if your chose number is right or not.
in example above you wrote (a+5b)^2, it means (a+5b)*(a+5b), why did you put 5b and 5b in other parenthesis? you could put (a+b)(a+25b) in other case, but because your number is 10ab, the possible number is 5b and 5b, if you multiply the inside numbers (5b*a) then add with the outside number (a*5b) you will get 10ab.
hope it helps.
2006-12-17 13:59:48
·
answer #4
·
answered by fortman 3
·
0⤊
0⤋
(a+5b)^2 = (a+5b)(a+5b) = a^2 + 5ab + 5ab + 25b^2 = a^2 + 10ab + 25b^2
Nothing has happened to it.
2006-12-17 13:49:21
·
answer #5
·
answered by Tom :: Athier than Thou 6
·
1⤊
0⤋
Just remember that you can't square a sum by squaring each part of the sum; you have to write it out and use FOIL.
(3 + 4)^2 is not 3^2 + 4^2
49 is not 9 + 16
2006-12-17 13:51:36
·
answer #6
·
answered by hayharbr 7
·
0⤊
0⤋
10ab = 2*a*5b
2 = first term
5b = second term
<>
2006-12-17 13:59:30
·
answer #7
·
answered by aeiou 7
·
0⤊
0⤋